Empirical social sciences and bioethics: Some reflections and an afterthought for Latin Americans - Lolas Stepke, Fernando (Acta Bioethica, 2002)
This paper emphasizes the need to integrate bioethical reflection with the results of empirical social sciences, defined as those disciplines which describe and predict behavior of individuals and groups and strive at general causality principles. Cultivating such disciplines enriches descriptive and prescriptive aspects of assertions regarding what is right and wrong and permits modulation of moral judgement. The goal is to analyze the influence of context on moral decision making and to submit to empirical study even the practice of bioethics. Finally, some observations are put forward on the convenience of developing a Latin American bioethics intellectually respectable and with the possibility of placing itself creatively in global thinking.